Salt Enhances Disease Resistance and Suppresses Cell Death in Ceramide Kinase Mutants. Issue 1 (26th June 2019) - Yang, Yu-Bing; Yin, Jian; Huang, Li-Qun; Li, Jian; Chen, Ding-Kang; Yao, Nan
Abstract : Salt inhibits cell death in acd5 mutants, partly via a mechanism that depends on salicylic acid–abscisic acid interactions, and enhances disease resistance, independent of pathogen-associated molecular pattern - triggered responses. Abstract: Sphingolipids act as structural components of cellular membranes and as signals in a variety of plant developmental processes and defense responses, including programmed cell death. Recent studies have uncovered an interplay between abiotic or biotic stress and programmed cell death. In a previous study, we characterized an Arabidopsis ( Arabidopsis thaliana ) cell-death mutant, accelerated cell death5 ( acd5 ), which accumulates ceramides and exhibits spontaneous cell death late in development. In this work, we report that salt (NaCl) treatment inhibits cell death in the acd5 mutant and prevents the accumulation of sphingolipids. Exogenous application of abscisic acid (ABA) and the salicylic acid (SA) analog benzothiadiazole demonstrated that the effect of NaCl was partly dependent on the antagonistic interaction between endogenous SA and ABA. However, the use of mutants deficient in the ABA pathway suggested that the intact ABA pathway may not be required for this effect. Furthermore, pretreatment with salt enhanced the resistance response to biotic stress, and this enhanced resistance did not involve the pathogen-associated molecular pattern-triggered immune response. Taken together, our findings indicate that salt inhibits sphingolipid accumulation and cell death in acd5 mutants partly via a mechanism that depends on SA and ABA antagonistic interaction, and enhances disease resistance independent of pattern-triggered immune responses.